PEMBELAJARAN MEMBACA TEKS BERITA SISWA KELAS XI SMA YAYASAN PEMBINA UNILA BANDARLAMPUNG - Uswatun Hasanah; Siti Samhati; Mulyanto Widodo (FKIP Universitas Lampung, 2013)
This research will be discussed about how the studying process of news text reading XI grade students. The aim of this research is to describe studying process of news text reading on students. This focused on the planning practicing, evaluating studying of news text reading. The method of this research is qualitative descriptive method. The data source is from news text reading activity. The data collecting technique are observing teacher’s and students’ activity, video recording, interview. And the data analyzing technique use flow models. The analysis includes three activities, data reduction, data presentasion, conclusion. The result of this research are lesson plan of news text reading students based on assessment learning plan instrument, implementation learning of news text reading based implementation process instrument of learning by teacher, students’ activity based on observation instruments. This research uses performance assesment technique as the evaluation.Masalah yang dibahas penelitian ini bagaimanakah proses pembelajaran membaca teks berita siswa kelas XI. Masalah penelitian bertujuan mendeskripsikan proses pembelajaran membaca teks berita siswa SMA , difokuskan pada perencanaan, pelaksanaan, evaluasi pembelajaran membaca teks berita. Metode penelitian menggunakan metode deskriptif kualitatif. Sumber penelitian kegiatan pembelajaran membaca teks berita siswa. Teknik pengumpulan data observasi aktivitas siswa, guru, rekaman video, wawancara. Teknik analisis data penelitian analisis data model alir. Analisis mencakup tiga kegiatan, reduksi data, penyajian data, penarikan kesimpulan. Temuan-temuan penelitian rencana pelaksanaan pembelajaran membaca teks berita siswa kelas XI, berdasarkan Instrumen Penilaian Perencanaan Pembelajaran, pelaksanaan pembelajaran membaca berita berdasarkan Instrumen Proses Pelaksanaan Pembelajaran oleh guru, aktivitas siswa berdasarkan Instrumen Observasi Aktivitas Siswa. Evaluasi digunakan pembelajaran membaca teks berita yakni teknik penilaian unjuk kerja.Kata kunci: instrumen, pembelajaran, teks berita.